The whole truth [compact disc, unabridged] - Baldacci, David (Hachette Audio, 2008)
In this international thriller, Nicholas Creel, the head of the Ares Corporation, a huge defense contractor, hires a perception management firm to start a second cold war by planting fake news stories on the Internet about Russian atrocities. A shadowy operative, A Shaw, allies himself with a disgraced female journalist in an effort to thwart Creel's evil plot.